Pengaruh Current Ratio, Return on Asset, Dan Debt to Equity Ratio Terhadap Harga Saham Perusahaan Pertanian Dalam Daftar Bei Tahun 2011-2020 - Amelia Angraini M; Nanu Hasanuh (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study, titled ‘The Influence of Current Ratio, Return On Assets, and Debt to Equity Ratio on Stock Prices of Agricultural Companies on the IDX List,’ aimed to see how financial indicators like current ratio, return on assets, and debt to equity affect stock prices. Secondary data for this study came from the BEI website in the form of yearly financial reports, as well as finance.yahoo.com for stock prices for agricultural enterprises. Purposive sample of three firms with a total of 30 data points is used in this investigation. The data analysis strategy may be carried out using the traditional assumption test analysis technique, the coefficient of determination (R2), and the hypothesis testing stage is carried out using the F-test and t-test with the data processing tool, SPSS version 16. According to the findings, the current ratio and debt to equity ratio have a partial negative and significant influence on the value of the stock price, whereas the return on assets has a partly negative and substantial effect on the value of the stock price. But when evaluated at the same time span, the results show the simultaneous effect of the ratio of the independent variables on dependent variable of stock prices, passively or actively thus leads to a reporting basis for its fundamental output.